An Investigation of Earnings Management Through Marketing Actions - Chapman, Craig J.; Steenburgh, Thomas J. (Management Science, 2011)
Prior research hypothesizes managers use “real actions,” including the reduction of discretionary expenditures, to manage earnings to meet or beat key benchmarks. This paper examines this hypothesis by testing how different types of marketing expenditures are used to boost earnings for a durable commodity consumer product that can be easily stockpiled by end consumers. Combining supermarket scanner data with firm-level financial data, we find evidence that differs from prior literature. Instead of reducing expenditures to boost earnings, soup manufacturers roughly double the frequency and change the mix of marketing promotions (price discounts, feature advertisements, and aisle displays) at the fiscal quarter-end when they have greater incentive to boost earnings. Our results confirm managers' stated willingness to sacrifice long-term value in order to smooth earnings and their stated preference to use real actions to boost earnings to meet different types of earnings benchmarks. We estimate that marketing actions can be used to boost quarterly net income by up to 5% depending on the depth and duration of promotion. However, there is a price to pay, with the cost in the following period being approximately 7.5% of quarterly net income. Finally, a unique aspect of the research setting allows tests of who is responsible for the earnings management. Although firms appear unable to increase the frequency of aisle display promotions in the short run, they can reallocate these promotions within their portfolio of brands. Results show firms shifting display promotions away from smaller revenue brands toward larger ones following periods of poor financial performance. This indicates the behavior is determined by parties above brand managers in the firm. These findings are consistent with firms engaging in real earnings management and suggest that effects on subsequent reporting periods and competitor behavior are greater than previously documented. This paper was accepted by Stefan Reichelstein, accounting.